Integrated Components of Intercultural Competence in English Language Teaching at College: Case Study - Muh Hesan; Slamet Setiawan; Ahmad Munir (IJET (Indonesian Journal of English Teaching), 2019)
In this global world, foreign language teaching has been demanded to be intercultural teaching which means that cultural teaching should be integrated in language teaching as well as language competence, in English language teaching for instance. On the ground that the importance of foreign language teaching and learning is largely for purpose of international communication, and intercultural knowledge has crucial role in successful communication. Therefore, this paper reports on a qualitative case study which investigates two English teachers’ practice of integrating intercultural competence in English language teaching at college level. Specifically, this paper provides analysis of intercultural components embedded in teachers’ practice of intercultural integration in teaching English. The data were collected through observation, and unstructured observational notes were employed. The observational data were analysed following sub-processes, are familiarizing, reducing, identifying and classifying, interpreting, and presenting. The result indicates that both English teachers’ understand the objective of English language teaching that teaching language is also teaching the culture as it is showed in their teaching process an intercultural integration, which includes some intercultural components such as attitudes, knowledge, and skills.